Пространственная семантика местных падежей коми языка (когнитивный анализ) - Кузнецов, Николай (2012)
It can be said that everything around us is located somewhere, moves from somewhere or to somewhere. This location or movement is given in relation to a certain landmark. One can move into an object, onto it, beneath it, before it etc., meaning that there are several spatial zones surrounding that object. Spatial relations are expressed in different ways in different languages. The Komi language first of all uses locative cases, which reflect both the zone where the movement occurs as well as its direction. In respect to the central meaning of the locative cases in Komi, these can be described as into-, in-, out of-, along-, towards-, from- and to-cases. In addition to these, there are six near-cases in Komi, referring to action that is happening near the landmark. Most of the locative cases in Komi have multiple meanings when expressing spatial relations. Depending on several circumstances their locative meanings may vary (Komi муын, for example, either means ‘on the ground’ or ‘in the soil’). The factors that influence the use of cases and their meaning can be language-internal or language-external. In fact, it is not important if the impacting factors are related to the language itself or not, as the way expressions are formed is the result of a person’s whole body of knowledge and experience. This concept is called encyclopaedic semantics and it is a feature of cognitive linguistics. Cognitive linguistics takes into account the cognitive patterns of human experience and looks at language in close relation to the human general understanding of the surrounding world and their knowledge, also making use of empirical data of other scientific disciplines. From the cognitive aspect, the multiple meanings of cases can be regarded as separate categories. These categories have their more representative, prototypical members and more peripheral members, which are all interlinked based on certain governing principles. This work is going to explore the spatial meanings of locative cases in the Komi language and their ...